A Modified Delphi Consensus on Optimal Pharmacological Management of Insomnia: Insights from a Malaysian Perspective - Ng, Chong Guan; Sulaiman, Ahmad Hatim; Talib, Nor Hazlin; Ismail, Ahmed Izuanuddin; Abd Rahsid, Rusdi; Tan, Maw Pin; Thirunavukarasu, Rajoo; Tan, Chong Tin (Malaysian Journal of Medical Sciences, 2025)
Insomnia represents a significant risk factor for impaired daytime functioning and a range of chronic health conditions and has emerged as a growing public health concern in Malaysia. The absence of standardised local guidelines complicates treatment decision-making. This consensus aimed to develop pharmacological treatment recommendations for insomnia in Malaysia using a modified Delphi approach. An eight-member expert panel comprising specialists in sleep medicine, psychiatry, neurology, and pharmacology reviewed high-level evidence on the neurobiology, diagnosis, and treatment of insomnia. A 31-item consensus statement survey addressing the definition, diagnosis, and pharmacological management of insomnia was conducted, with agreement evaluated using a five-point Likert scale. The consensus recommendations were finalised after two Delphi rounds and a final vote, with at least 75% agreement required for each statement. Consensus statements highlighted the need for tailored treatment strategies in Malaysia that combine nonpharmacological and pharmacological interventions. Insomnia was recognised as a chronic condition diagnosed primarily using subjective criteria, with sleep diaries and questionnaires recommended as assessment tools. Benzodiazepines, Z-class drugs, and dual orexin receptor agonists (DORAs) were found to be effective; however, concerns regarding long-term safety and dependency were noted. DORAs demonstrated promise in managing both sleep onset and maintenance, with lemborexant highlighted as a promising pharmacological option. The meeting emphasised the importance of individualised treatment plans and careful risk assessment, particularly for older adults, and provided practical recommendations for the management of insomnia. The integration of Cognitive Behavioural Therapy for Insomnia with pharmacotherapy was strongly advocated. These consensus statements offer a practical foundation for the development of future national guidelines to enhance insomnia care in Malaysia’s primary care settings.